1990
DOI: 10.1128/mcb.10.10.5541
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression and DNA-binding activity of transcription factor Sp1 in doxorubicin-resistant HL-60 leukemia cells.

Abstract: The processes responsible for the multidrug-resistant (Mdr) phenotype in Adriamycin (doxorubicin)-resistant HL-60 leukemia cells (HL-60/AR) are not defined. Since enhanced transcription of resistance-related proteins is associated with Mdr cells, we sought to determine whether changes in the expression of specific transcription factors were a feature characteristic of the Mdr process. Nuclear extracts were prepared from wild-type and resistant cells and compared for their ability to bind DNA consensus sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 34 publications
5
20
0
Order By: Relevance
“…Our results are, in fact, consistent with data from other systems showing that Sp1 binding is repressed by phosphorylation and that removal of phosphate groups from Sp1 enhances binding to DNA (33)(34)(35)(36)(37)(38)(39). However, it is possible that phosphorylation of Sp1 or Sp1-like proteins could enhance the ability of Sp1 to form an active transcriptional complex with other nuclear factors.…”
Section: Sp1 Is Required For the Elevated Levels Of Ctgf Expression Osupporting
confidence: 82%
“…Our results are, in fact, consistent with data from other systems showing that Sp1 binding is repressed by phosphorylation and that removal of phosphate groups from Sp1 enhances binding to DNA (33)(34)(35)(36)(37)(38)(39). However, it is possible that phosphorylation of Sp1 or Sp1-like proteins could enhance the ability of Sp1 to form an active transcriptional complex with other nuclear factors.…”
Section: Sp1 Is Required For the Elevated Levels Of Ctgf Expression Osupporting
confidence: 82%
“…46,47 The reduced levels of Sp1 binding with TNF-␣ stimulation could also be attributable to TNF-␣-induced Sp1 phosphorylation ( Figure 7B) because Sp1 phosphorylation could reduce Sp1 binding 48 and dephosphorylation of Sp1 has been suggested to enhance Sp1 DNA binding activity. 49 In DSS-treated mice, we found that DSS does not alter overall nuclear levels of Sp1, similar studies showed that TNF-␣ did not change Sp1 expression 30 but increased NF-B (p65) expression. 50 Similarly, DSS treatment can up-regulate the expression of NF-B (p65) in colon epithelial cells, and more importantly, DSS treatment can translocate p65 protein into nucleus as active form, which suggests that the increased expression of SPAK might be attributable to the increased nuclear protein NF-B (p65).…”
Section: Discussionsupporting
confidence: 51%
“…Nuclear extracts were prepared from a pre-promyelocytic K562 leukaemia cell line (Borellini et al, 1991) as described previously (Prywes & Roeder, 1986) except that protease inhibitors were added to the hypotonic buffer as well as the nuclear suspension buffer (Borellini et al, 1991) and an additional step of concentrating nuclear extract by ammonium sulphate precipitation (0n33 g\ml) was included (Shapiro et al, 1988). The protein concentration (" 8 mg\ml) was measured using a kit from Bio-Rad (Hercules).…”
Section: Methodsmentioning
confidence: 99%